Genetic Fine Structure of a Salmonella enterica Serovar Typhi Strain Associated with the 2005 Outbreak of Typhoid Fever in Kelantan, Malaysia - Baddam, Ramani; Kumar, Narender; Thong, Kwai Lin; Ngoi, Soo Tein; Teh, Cindy Shuan Ju; Yap, Kien Pong; Chai, Lay Ching; Avasthi, Tiruvayipati Suma; Ahmed, Niyaz (American Society for Microbiology, 2012)
Among enteric pathogens, Salmonella enterica serovar Typhi is responsible for the largest number of food-borne outbreaks and fatalities. The ability of the pathogen to cause systemic infection for extended durations leads to a high cost of disease control. Chronic carriers play important roles in the evolution of Salmonella Typhi; therefore, identification and in-depth characterization of isolates from clinical cases and carriers, especially those from zones of endemicity where the pathogen has not been extensively studied, are necessary. Here, we describe the genome sequence of the highly virulent Salmonella Typhi strain BL196/05 isolated during the outbreak of typhoid in Kelantan, Malaysia, in 2005. The whole-genome sequence and comparative genomics of this strain should enable us to understand the virulence mechanisms and evolutionary dynamics of this pathogen in Malaysia and elsewhere.